Reflection of Religious Intolerance Myth in Video Construction â€œSayyid El-Raisâ€ Based on Barthes Perspective - Erwhintiana, Ifi; Fitriani, Laily (Universitas Negeri Semarang, 2021)
This research aims to develop denotative and connotative meanings in sayyid El-Rais' videos, as well as reveal myths based on Barthes's perspective. This research is a qualitative descriptive research. Data collection technique used observation and taking notes technique. Researchers used descriptive analysis techniques based on the Miles and Huberman model are data reduction, data presentation, and conclusions. The results showed that reading of first level in semiotics perspective produced several codes that referred to text structure including; symbolic, semantic, and hermeneutic. Denotatively, the speech in video reflect outpouring of a Palestinian child about incidents that happened to him, called deprived homeland. The second level reading that refers to code development resulted in a myth of religious tolerance. In connotative meaning, there are portraits of religious intolerance that are carried in these stories. This speech presents as religious intolerance representation felt by the Palestinian people so that the author's message that can be taken through this portraits is able to increase awareness of religious tolerance and empathy for others as humanity form